Industrial Invention: Heroic, or Systematic? - Epstein, Ralph C. (Quarterly Journal of Economics, 1926)
I. Purpose of this paper: to survey the literature, to examine current practice, and to classify the facts needed for a tenable theory, 233. — II. The heroic explanation, commonly found in biographies, 237. — Inventive abilities not so rare as commonly supposed, 241. — III. Theories of successive increments, 242. — Cumulative character of contribution and discovery, 243. — This intensified by our greater willingness both to accept and to give, 251. — IV. Organized industrial research and invention on the part of large corporations, 253. — Methods by which new devices are developed, 255. — Cooperative character of the procedure, 258. — V. Materialistic explanations, 260. — The profit motive not so essential in some instances as in others, 266. — The real question: what proportion of usable inventions comes from professional inventors? 268. — VI. Conclusion: what sort of inductive study is needed, 269.